Sciences and audiences along the lastcentury: the impact of Astronomy Education - Barros, Rosario Magdalena; Garcia, Beatriz Elena (Cambridge University Press, 2020)
Fil: Barros, Rosario Magdalena. Universidad Politécnica de Catalunya; España